Math, asked by lovelysmriti900, 1 year ago

detailed answers of this question​

Attachments:

Answers

Answered by rishu6845
3

Given----> A and H are the AM and HM between a and b .

To prove---->

{( a - A ) / ( a - H ) } × { ( b - A ) / ( b-H ) = A / H

Proof----> Plzzz see the attachement .

1) We know that AM and HM between p and q are

AM = ( p + q ) / 2 and

HM = 2pq / ( p + q )

Using this we find value of A and H .

Putting this in LHS, and solving we get RHS.

Additional information---->

1) Geometric mean between a and b

GM = √(ab)

Attachments:

EliteSoul: Awesome !
Similar questions